Implementasi Pendidikan Karakter dalam Kurikulum 2013 - Rambe, Anggi Afrina; Dwietama, Regita Ayu; Arya Rahardja, Muhammad Nurfaizi; Firdaus, Endis; Rahman, Rini; Suresman, Edi (UIR Press, 2024)
This study aims to analyze the implementation of character education in Curriculum 2013 at SDN 16 Rantau Utara. The importance of character education in forming a young generation that is not only academically intelligent but also has strong moral values. This research uses a qualitative case study method, with data collection using observation, interviews and document analysis to collect data from teachers and learners. The results show that character education is integrated into various subjects, focusing on teaching moral values through active learning methods. Although there are challenges in character assessment and evaluation, many teachers strive to overcome these problems by applying innovative methods. Therefore, the implementation of character education in Curriculum 2013 has shown significant progress, but it still needs improvement in terms of the assessment system in order to objectively measure students' character development. Thus, character education in Curriculum 2013 is expected to be more effective in creating students who excel academically and have good character.